Amniotic Tissue Modulation of Knee Pain—A Focus on Osteoarthritis - Hannon, Charles P.; Yanke, Adam B.; Farr, Jack (The Journal of Knee Surgery, 2019)
The use of intra-articular therapies as sources of growth factors, anti-inflammatory mediators, and medicinal signaling cells for osteoarthritis (OA) is rapidly evolving. Amnion, chorion, amniotic fluid, and the umbilical cord are distinct placental tissues that have been investigated for use in OA. Amniotic membrane (AM) synthesizes a variety of growth factors, cytokines, and vasoactive peptides that modulate inflammation. In addition, they contain amniotic epithelial cells and amniotic mononuclear undifferentiated stromal cells, which have chondrogenic and osteogenic differentiation capacity. AMs are also rich sources of hyaluronic acid and proteoglycans, which could play a role in the potential therapeutic relief of OA. Currently, there are several commercially available formulations of AM that differ based on content as well as how they were preserved. Understanding the processing of amniotic tissue is important because of their distinct mechanical and biologic effects of preservation on AM grafts. To date, there have been two preclinical and only one clinical study on the use of AM for OA, which show promising results. Many high level of evidence clinical trials are currently underway investigating the use of AM of OA. Future basic science and clinical research is warranted to better understand the anti-inflammatory and chondroregenerative properties of amniotic tissue and to determine clinically what amniotic tissue product is most efficacious for symptomatic OA.
Keywords: cartilage; osteoarthritis; amniotic suspension allograft; amniotic membrane; amniotic fluid